Multicultural Da'wah in Pekalongan City - Sofa Aulia Fauziah (Advances In Social Humanities Research, 2026)
Pekalongan City has the largest fishing port on the island of Java, which has become a trading center, attracting many newcomers to settle in the area. The Javanese, Arab, and Chinese ethnicities live side by side in harmony and mutual tolerance. Given the uniqueness of Pekalongan's diverse community, this mini-research employs a qualitative method through a literature review of journals, books, and other relevant sources. This study aims to understand how multicultural da'wah methods are carried out by the Javanese, Arab, and Chinese Muslim ethnicities in Pekalongan City, as well as how the media approach using batik, the city's identity, is utilized. This research employed a qualitative approach using library research. Data were collected from academic books, journal articles, theses, official documents, and other relevant literature concerning multiculturalism, intercultural communication, and Islamic da'wah. Data were analyzed using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings indicate that the methods of dakwah bil hal, dakwah bil lisan, and dakwah bil qalam are employed by these ethnic groups to invite others to Islamic teachings, alongside an intercultural da'wah approach using batik as a medium of da'wah. Multicultural da'wah in Pekalongan demonstrates that Islamic preaching can be effectively conducted within a diverse social setting by respecting cultural differences while maintaining Islamic values. The harmonious interaction among Javanese, Arab, and Chinese Muslim communities contributes significantly to the sustainability of religious tolerance and social cohesion.